2014
DOI: 10.5296/jsss.v1i2.5099
|View full text |Cite
|
Sign up to set email alerts
|

Corporal Punishment as a Parental Practice and Anxiety in Pre-adolescent Children

Abstract: Corporal punishment is the physical punitive measures of parents against children with devastating consequences when bordering on child abuse. This has even led to legislation against corporal punishment while controversy and criticism divides researchers and practitioners as to the prohibition against moderate and functional corporal punishment which may act as an effective method of education. Limited research exists on corporal punishment and its effect on the emotional aspects of children and investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Adverse childhood experiences and early interpersonal difficulties have been linked with emotional distress in adulthood (Oshio et al 2013), and serious family dysfunctionsuch as domestic violencewith subsequent mental and somatic problems (Arnow 2004). Several studies have also found specific associations between childhood physical punishmentsuch as pushing, grabbing, shoving, slapping, hittingand difficulties in later psychological, physical or social development (Afifi et al 2012;Breen et al 2015;Gershoff 2002;Osterman et al 2014;Yaffe and Burg 2014). A meta-analysis by Ferguson (2013) indicated minor, but significant longitudinal relationships between corporal punishment and several negative long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse childhood experiences and early interpersonal difficulties have been linked with emotional distress in adulthood (Oshio et al 2013), and serious family dysfunctionsuch as domestic violencewith subsequent mental and somatic problems (Arnow 2004). Several studies have also found specific associations between childhood physical punishmentsuch as pushing, grabbing, shoving, slapping, hittingand difficulties in later psychological, physical or social development (Afifi et al 2012;Breen et al 2015;Gershoff 2002;Osterman et al 2014;Yaffe and Burg 2014). A meta-analysis by Ferguson (2013) indicated minor, but significant longitudinal relationships between corporal punishment and several negative long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In one Finnish cross-sectional study, frequent corporal punishment in childhood was associated with depression and other mental health problems during adulthood (Osterman et al 2014). Although the adverse effects of physical punishment have led to legislation against corporal punishment in many countries, some researchers and professionals still disagree about the advantages of moderate corporal punishment as an effective method of education (Yaffe and Burg 2014).…”
Section: Introductionmentioning
confidence: 99%